Towards an automatic approach to estimating test effort: An Experience Report - de Sousa, Amanda Oliveira; Santos, Ismayle de Sousa; Aragão, Bruno Sabóia; Andrade, Rossana Maria de Castro (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Testing is a key activity to increase the quality of a software development project. However, this activity presents challenges, such as estimating the effort required to test software. Test estimates are sometimes performed based on experience, which may make the estimation inaccurate. In this paper, an experiment report is presented on the application of a semiautomatic approach to the estimation of the test effort, with the objective of systematizing the process of estimating the test effort and, at the same time, generating estimates closer to the actual effort spent. The approach was applied in a test factory and the estimated times were close to the actual effort, indicating that the approach used is promising.